Metabolic repair through emergence of new pathways in Escherichia coli. (November 2018) - Pontrelli, Sammy; Fricke, Riley; Teoh, Shao; Laviña, Walter; Putri, Sastia; Fitz-Gibbon, Sorel; Chung, Matthew; Pellegrini, Matteo; Fukusaki, Eiichiro; Liao, James
Abstract Escherichia coli can derive all essential metabolites and cofactors through a highly evolved metabolic system. Damage of pathways may affect cell growth and physiology, but the strategies by which damaged metabolic pathways can be circumvented remain intriguing. Here, we use a ΔpanD (encoding for aspartate 1-decarboxylase) strain of E. coli that is unable to produce the β-alanine required for CoA biosynthesis to demonstrate that metabolic systems can overcome pathway damage by extensively rerouting metabolic pathways and modifying existing enzymes for unnatural functions. Using directed cell evolution, rewiring and repurposing of uracil metabolism allowed formation of an alternative β-alanine biosynthetic pathway. After this pathway was deleted, a second was evolved that used a gain-of-function mutation on ornithine decarboxylase (SpeC) to alter reaction and substrate specificity toward an oxidative decarboxylation–deamination reaction. After deletion of both pathways, yet another independent pathway emerged using polyamine biosynthesis, demonstrating the vast capacity of metabolic repair. In response to the deletion of key genes involved in biosynthesis of the essential CoA precursor β-alanine, Escherichia coli overcomes this pathway damage by successively evolving alternative metabolic pathways.